(untitled) (SCAFFOLD: A SHOWCASE OF VANDERBILT FIRST-YEAR WRITING, 2021)
Written for a first-year writing seminar in Islamic law, this essay investigates a recent trend in the history of Islamic Jurisprudence; the digital fatwa. In the context of accessible internet services becoming available to worldwide Muslim communities, digital fatwas have become increasingly popular, allowing everyday Muslims to pose questions both major and minute before Islamic jurists. Utilizing a case study-esque structure – specifically analyzing e-fatwas on marijuana and democratic participation respectively – comparisons are drawn between the methodologies and outcomes of contemporary American and Arabic Islamic jurists online. For additional context, listen to the author’s reflection on the piece below.